Comparative investigation of the utilisation of microsilica and GGBS in reducing the chloride ingress in concrete / Rosmida Ab Ghani - Ab Ghani, Rosmida (1998)
The compressive strength and durability are two most important characteristic of concrete. The strength development and durability of concrete can be measured and indicated by testing. This project paper represents die results of research on the influence of partial replacements of OPC by nucrosilica and compared with GGBS for grade 20 N/mm2 concrete with respect to the strength development and resistance to chloride ingress. For the microsilica, the experimental programme comprised of five replacement levels namely 0%, 4%, 8%, 12% and 16% and for the GGBS are 0%, 40%, 60%, 75% and 90%. The 0% replacement is employed as control mix. The percentage replacements is based on optimum replacement of the material for the strength developments The cube size for strength development are 100mm x 100mm and the test was carried at 3, 7, 28 and 90 days after curing in water. While the chloride diffusion test was done on a 100mm x 100mm x 500mm prism immersed in a container containing sodium chloride (Na CI) solution concentration equivalent to mat of seawater ( 19380 ppm CI). To determine the depth of penetration, the prism were split in the transverse direction and droplets of 0.1 N stiver nitrate (AgNQj ) solution was applied to the split surface